City-scale assessment of long-term air quality impacts on the respiratory and cardiovascular health - Šulc, Libor; Gregor, Petr; Kalina, Jiří; Mikeš, Ondřej; Janoš, Tomáš; Čupr, Pavel (Frontiers in Public Health, 2022)
Background: The impact of the urban environment on human health is a contemporary subject of environmental research. Air pollution is often considered a leading environmental driver. However, a plethora of other factors within the urban exposome may be involved. At the same time, the resolution of spatial data is also an important facet to consider. Methods: Generalized linear models were utilized to find the associations between respiratory and cardiovascular health conditions and air quality (PM10, PM2.5, NO2, benzene, SO2) in high sub-city scale spatial resolution. Socio-economic indicators and built-up area indicators were also included in the analysis. Results: Statistically significant associations between air pollution and the health of the urban population were found. The strongest association was between benzene and the incidence of bronchitis in the adult population (RR 1.552 95% CI [1.369-1.765] per 0.5 µg/m3 change in benzene concentration). A similar relation was observed between NO2 and the same health condition (RR 1.483 95% CI [1.18-1.857] per 8.9 µg/m3 of change in NO2). Other weaker associations were also found between asthma in children and PMs, NO2, or benzene. Cardiovascular-related hospitalizations in the general population were linked with NO2 (RR 1.218 95% CI [1.12-1.323] per 9.7 µg/m3 change in NO2). The remaining pollutants were slightly less but still significantly associated with cardiovascular-related hospitalizations. Conclusion: Our findings are mostly highly statistically significant (p≤0.001) and are in line with current literature on the adverse effects of air pollution on the human population. The results highlight the need for continual improvements in air quality. Further research involving other variables is an essential step towards understanding the complex urban exposome and its implications for human health. An increase in data spatial resolution is especially important in this respect as well as for improving city health risk management.